Simulasi WinAir4 (CFD) Terhadap Pengaruh Kecepatan Dan Aliran Udara Di Dalam Ruang Kuliah Universitas Nusa Nipa Maumere - Maria Carolin Tandafatu; Cornelia Hildegardis (Fakultas Teknik Universitas Cenderawasih, 2022)
Comfort can be provided from a building, inseparable from the existence of the building itself in the context of an environment that is limited by consideration of natural factors. In an effort to achieve comfort in buildings in tropical climates such as Indonesia, especially the city of Maumere, with characteristics of wind speed, humidity and relatively high air temperature and solar heat radiation can reach levels outside the human comfort zone. This study compares the speed and direction of wind flow in different lecture halls, seen from the level of height, direction and contour of the ground. The method used is data taken using equipment measured in the field and the results are simulated using WinAir4 from ECOTEC. The results obtained are the effect of altitude level, direction and contour orientation on wind speed and air flow in the design of the lecture hall in relation to thermal comfort.